Euro on trial : to reform or split up? - Brown, Brendan, 1951- (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2004)
Looks back - to the aspirations of the founders - and also forward - to the possibility of reform or splitting up of the European Monetary Union.
Includes bibliographical references (p. 173-175) and index.
oif 19/08/15
Loan
Keywords: Monetary unions -- European Union countries; Monetary policy -- European Union countries; European Union countries -- Economic policy; Economic and Monetary Union